The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11239-010-0548-3
|View full text |Cite
|
Sign up to set email alerts
|

Early stroke-related deep venous thrombosis: risk factors and influence on outcome

Abstract: Deep venous thrombosis (DVT) is a serious complication of various medical conditions including acute stroke. Our aim was to identify the occurrence of early stroke-related DVT, risk factors for its development and the influence on outcome. The study involved consecutive patients admitted to our center due to acute ischaemic (n = 278) or haemorrhagic (n = 12) stroke during a 16-month period. We collected data on their pre-stroke health status, neurological deficit on admission and baseline serum CRP and fibrino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 30 publications
3
66
1
Order By: Relevance
“…Thirdly, the primary outcome in the final multivariate model was the presence of DVTs in any location, including proximal and distal DVT. The application of ultrasound has been shown to offer a limited way of detecting small and distal DVTs (63.5 vs. 94.2%) . Given the fact there is a lack of consensus on the clinical significance of symptomatic isolated distal DVT, further studies should focus on both proximal and distal DVT detection using more advanced diagnostic technology .…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the primary outcome in the final multivariate model was the presence of DVTs in any location, including proximal and distal DVT. The application of ultrasound has been shown to offer a limited way of detecting small and distal DVTs (63.5 vs. 94.2%) . Given the fact there is a lack of consensus on the clinical significance of symptomatic isolated distal DVT, further studies should focus on both proximal and distal DVT detection using more advanced diagnostic technology .…”
Section: Discussionmentioning
confidence: 99%
“…34 There is often a delay in presenting with a stroke and there will always be some delay in applying VTE prophylaxis because the patients need to be assessed and the treatment started. In addition, in a randomised trial there may be additional delays because of the time taken to obtain consent and enrol the patients.…”
Section: Does Delay In Applying Intermittent Pneumatic Compression Immentioning
confidence: 99%
“…According to the Virchow's triad, VTE is a condition that results from altered blood coagulation, stasis or abnormalities in the vessel wall [11,12]. Previous studies have identified multiple risk factors for VTE, including age, previous VTE episodes and cerebrovascular disease (CVA) [13][14][15]. Diabetes, leg fractures, major surgery and certain cancers are also associated with increased risk of VTE [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%